A randomised comparison of bolus phenylephrine and ephedrine for the management of spinal hypotension in patients with severe preeclampsia and a non-reassuring fetal heart rate trace - Adams, Samantha (Department of Anaesthesia and Perioperative Medicine, 2019)
Background: Studies in healthy patients undergoing elective caesarean delivery show that ephedrine used for spinal hypotension is associated with increased fetal acidosis compared with phenylephrine. This has not been investigated prospectively in severe preeclampsia. Methods: Patients with severe preeclampsia requiring caesarean delivery for a non- reassuring fetal heart tracing were randomised to receive bolus ephedrine (7.5-15 mg) or phenylephrine (50-100 μg) for spinal hypotension. The primary outcome was umbilical arterial base deficit. Secondary outcomes were umbilical arterial (UA) and venous (UV) pH and lactate level, venous base deficit, and Apgar scores. Results: A total of 133 women were included;; 64 required vasopressor treatment and were randomised to 2 groups of 32 with similar patient characteristics. Pre- delivery blood pressure changes were similar in the 2 groups. There was no difference in mean [SD] UA base deficit (-4.9 [3.7] vs -6.0 [4.6] mmol·L⁻¹ for ephedrine and phenylephrine respectively;; P = 0.29). Mean [SD] pH (UA and UV) and lactate levels were also similar between groups (7.25 [0.08] vs 7.22 [0.10], 7.28 [0.07] vs 7.27 [0.10], and 3.41 [2.18] vs 3.28 [2.44] mmol·L⁻¹ respectively). In addition, UV PO₂ was higher in the ephedrine group (2.8 [0.7] vs 2.4 [0.62]) kPa, P = 0.02). There was no difference in 1- or 5-minute Apgar scores, numbers of neonates with 1-minute Apgar scores < 7 (10/32 [31%] vs 12/32 [38%]), or with a pH < 7.2 (6/31 [19%] vs 8/29 [28%]). Conclusions: In patients with severe preeclampsia and fetal compromise, fetal acid-base status is independent of the use of bolus ephedrine vs phenylephrine to treat spinal hypotension.